Neutrophil elastase (Elane) may serve as a potential therapeutic target in inflammatory bowel disease-associated growth attenuation: focus on the epiphyseal growth plate in young male rats - Menahem, Chen; Foist, Michal; Shtaif, Biana; Bar-Maisels, Meytal; Meivar-Levy, Irit; Phillip, Moshe; Gat-Yablonski, Galia (Frontiers in Endocrinology, 2025)
IntroductionGrowth is frequently compromised in children with inflammatory bowel disease (IBD). With the prevalence of pediatric IBD having doubled over the past 25 years, growth failure poses a major additional challenge in managing the disease. Despite the use of conventional treatments: growth hormone, glucocorticoids, anti-inflammatory cytokine therapies, and bowel resection—growth impairment often persists, and some therapies may even worsen the condition. A deeper understanding of the underlying mechanisms affecting the epiphyseal growth plate (EGP) is essential for developing new therapies to address IBD-related growth attenuation. In the current study we investigated the mechanisms by which dextran sulfate sodium (DSS)-induced colitis impairs growth at the EGP. DSS is a widely utilized model for investigating the pathophysiology of IBD, however, the effect on linear growth was not reported.MethodsYoung male SD rats were treated with 1% DSS in the drinking water. Body weight, colon and humerus length, and EGP height were measured. Total RNA extracted from the EGPs was used for RNA sequencing. ATDC5 cell culture was used to confirm the results.ResultsExposure to DSS led to a marked decrease in both body weight (by 20%) and colon length (by 30%). The height of the EGP was reduced by 23%, with comparable reductions in both the proliferative and hypertrophic zones. Transcriptomic analysis revealed an upregulation of immune-related genes, with neutrophil elastase (ELANE) being particularly prominent. Gene set enrichment analysis indicated downregulation of oxidative phosphorylation pathways and upregulation of cell cycle pathways, pointing to disruptions in core cellular processes such as replication and metabolism within EGP cells. In vitro studies supported the RNA sequencing results, showing that ELANE expression is inducible by inflammatory stimuli.DiscussionThese findings suggest that immune-related genes are actively expressed in the EGP in response to systemic inflammation. Importantly, ELANE was found to be endogenously expressed in chondrocytes and upregulated under inflammatory conditions, indicating a potential intrinsic chondrocyte-mediated mechanism contributing to inflammation-induced growth attenuation. Our study introduces a novel mechanism through which chronic inflammation may directly hinder skeletal growth. This intrinsic ELANE expression, together with the upregulation of MMP13, indicates a direct catabolic impact on the extracellular matrix.